TDP-43 pathology is associated with divergent protein profiles in ALS brain and spinal cord - Emily Feneberg; Alexander G. Thompson; Philip D. Charles; Iolanda Vendrell; Benedikt M. Kessler; Roman Fischer; Olaf Ansorge; Elizabeth Gray; Kevin Talbot; Martin R. Turner (Acta Neuropathologica Communications)
Abstract Neuronal and glial cytoplasmic inclusions positive for TAR DNA-binding protein 43 (TDP-43) are the defining pathological hallmark of 97% of amyotrophic lateral sclerosis (ALS) and 50% of frontotemporal dementia (FTD). The ALS-FTD clinicopathological spectrum variably involves cortical and spinal anterior horn cell pathology. The broader protein composition of these inclusions is of major importance to understanding pathogenesis, clinical heterogeneity and biomarker development. This study examined the proteome associated with TDP-43 inclusions in ALS, using mass spectrometry-based proteomic analysis of spinal cord and cerebral cortex from donors with phosphoTDP-43 positive ALS (n = 16), alpha-synuclein positive Parkinson’s disease (PD, n = 8), phosphotau and beta-amyloid positive Alzheimer’s disease (AD, n = 8) and age matched non-neurological controls (n = 8), comparing ALS with non-ALS conditions, spinal cord with cerebral cortex samples, and detergent-soluble with -insoluble fractions. Increased abundance of TDP-43 in the detergent-insoluble fraction of ALS cortex and spinal cord tissue confirmed disease-specific protein enrichment by serial fractionation. The most striking alterations between ALS and other conditions were found in the detergent-insoluble fraction of spinal cord, with predominant enrichment of endosomal and extracellular vesicle pathways. In the cortex mitochondrial membrane/envelope and ion transmembrane transport pathways were enriched in the detergent-insoluble fraction. RNA/DNA metabolic processes (in spinal cord) versus mitochondrial and synaptic protein pathways (in cortex) were upregulated in the detergent-soluble fraction of ALS cases and downregulated in the insoluble protein fraction. Whilst motor cortex and spinal cord may not optimally reflect disease-specific pathways in AD, in PD a significant enrichment of alpha-synuclein in the detergent-insoluble fraction of spinal cord was found. Among proteins concordantly elevated in the detergent-insoluble fractions of spinal cord and cortex, there was greater representation of proteins encoded by ALS-associated genes, specifically Cu/Zn superoxide dismutase 1, valosin containing protein and TDP-43 (odds ratio 16.34, p = 0.002). No significant increase in TDP-43 interacting proteins was observed in either detergent-soluble or -insoluble fractions. Together, this study shows a divergence in the composition of proteins associated with TDP-43 positive detergent-insoluble inclusions between spinal cord and cerebral cortex. A common upregulation of proteins encoded by ALS-causing genes implicates their role in the pathogenesis of the ALS-FTD spectrum of diseases beyond TDP-43. Data are available via ProteomeXchange with identifier PXD067060.